Insulin signaling and its application - Le, Thi Kim Chung; Dao, Xuan Dat; Nguyen, Dang Vung; Luu, Duc Huy; Bui, Thi Minh Hanh; Le, Thi Huong; Nguyen, Huu Thang; Le, Tran Ngoan; Hosaka, Toshio; Nguyen, Thi Thu Thao (Frontiers in Endocrinology, 2023)
The discovery of insulin in 1921 has exerted a new branch of research into insulin activity and insulin resistance. Many discoveries in this field have been applied to diagnosing and treating diseases related to insulin resistance. In this mini-review, the authors attempt to synthesize the updated discoveries to unravel the related mechanisms and inform the development of novel applications. Firstly, we depict the insulin signaling pathway to explain the physiology of insulin action, starting at the receptor sites of insulin and downstream signaling of the insulin signaling pathway. Based on this, the next part will analyze the mechanisms of insulin resistance with two major provenances: the defects caused by receptors and the defects due to extra-receptor causes but here focus on post-receptor causes. Finally, we inform the recent applications including the diseases related to insulin resistance (obesity, cardiovascular disease, Alzheimer’s disease, and cancer) and the potential treatment of those based on insulin resistance mechanisms.